Iran's relations with the Arab states of the gulf common interests over historic rivalry - Warnaar, Maaike; Zaccara, Luciano; Aarts, Paul 1949- (Gulf Research Center book series, 2016)
This is not limited to the ongoing disputes in the Gulf, one of the most important strategic locations globally. Iran and the GCC states also find themselves on opposing sides in the Syrian and to some extent the Iraqi conflicts. This volume traces the origins of the troubled relations between Iran and the majority of the GCC monarchies. It discusses not only geostrategic rivalries, but also matters of identity which have been of increased importance since 2010. While important differences are noticeable among the GCC monarchies in regard to their willingness to engage Iran, the difficult relationship between Saudi Arabia and Iran puts a strain on the possibilities for engagement between Iran and the GCC as a whole.